A Case of a 50-Year-Old Woman with Typical Fabry Disease Who Showed Serial Electrocardiographic and Echocardiographic Changes over a 17-Year Period - Su Nam Lee; Gee-Hee Kim; Ki-Dong Yoo (Case Reports in Cardiology)
Fabry disease (FD) is a progressive, X-linked lysosomal storage disorder caused by a deficiency of α-galactosidase A activity. Affected individuals accumulate globotriaosylceramide and glycosphingolipids in the lysosomes and cytoplasm of cells throughout the body, leading to major organ failure and premature death. Cardiac involvement includes left ventricular hypertrophy, arrhythmia, endothelial dysfunction at vascular wall, and cardiomyopathy. The diagnosis of FD can be difficult and there is often a long lag time between symptoms and diagnosis. Here, we present a case of a 50-year-old woman with typical Fabry disease who showed serial electrocardiographic and echocardiographic changes over 17 years prior to diagnosis with Fabry disease.